Role of FAST in blunt trauma abdomen: A promising diagnostic tool to evaluate management in patients and comparison of its accuracy with CT and laparotomy - Brij Mohan Singh Pokhariya; Sachin Kumar Karnwal (Asian Journal of Medical Sciences, 2023)
Background: Focused assessment with sonography for trauma (FAST) is a limited ultrasound examination directed solely at identifying the presence of free intraperitoneal or pericardial fluid. In the context of traumatic injury, free fluid is usually due to hemorrhage and contributes to the assessment of the circulation. Performed in the trauma room by properly trained and credentialed staff, it allows the timely diagnosis of potentially life-threatening hemorrhage and is a decision-making tool to help determine the need for transfer to the operating room, computed tomography (CT) scanner, or angiography suite. The FAST scan is a 4 view scan reliant on detecting the presence of fluid within the pericardium and most dependent zones of the peritoneum in the horizontal patient. It is capable of detecting more than 100–250 mL of free fluid. CT scanning, in comparison, is capable of detecting more than approximately 100 mL of free fluid in the abdominal cavity. As a “rule of thumb,” a rim of 0.5 cm of fluid in Morison’s pouch represents approximately 500 mL of free fluid, and a 1 cm rim represents approximately 1000 mL. Aims and Objectives: The aims of this study were as follows: Role of FAST in blunt trauma abdomen: A promising diagnostic tool to evaluate management in patients and comparison of its accuracy with CT and laparotomy. Materials and Methods: The FAST scan was performed by Color Doppler Siemens Sonoline G-50 machine using either 2–5 MHz convex transducers or 5–10 MHz linear transducer department of Radiology L.L.R. Hospital, Kanpur. At FAST examines four areas for free fluid, perihepatic and hepatorenal space, perisplenic, and pelvis pericardium. Results: Sensitivity of FAST: 87.5%, specificity of FAST: 75%, and negative predictive value (NPV) of FAST are 80%. CT scan had sensitivity of: 97%, specificity of: 95%, and positive predictive value of CT scan: 92% NPV of: 100%. Laparotomy was GOLD standard with specificity of 100%. Conclusion: FAST was positive in 62.5% cases of blunt trauma abdomen. Sensitivity of FAST: 87.5%, specificity of FAST: 75%, and NPV of FAST are 80%. CT scan had sensitivity of: 97%, specificity of: 95%, positive predictive value of CT scan: 92%, and NPV of: 100%. Laparotomy was GOLD standard with specificity of 100%.